2022
DOI: 10.3389/fenvs.2022.1012838
|View full text |Cite
|
Sign up to set email alerts
|

Runoff simulation and projection in the source area of the Yellow River using the SWAT model and SSPs scenarios

Abstract: The source area of the Yellow River (SAYR) is one of the world´s largest wetlands containing the greatest diversity of high altitude marshlands. For this reason, its response to climate change is extremely significant. As revealed by different studies, the response of hydrological processes to global warming results in high uncertainties and complexities in the water cycle of the SAYR. Thus, understanding and projecting future runoff changes in this region has become increasingly important. In the present inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…6,(a) ). Though the precipitation increment identified in the distant future might result in the flow rate increment, the temperature increment might also result in intensified evapotranspiration, which should lead to a slight peak flow rate decline in the distant future [ 77 ]. Refer to Icyimpaye, [ 79 ] and Icyimpaye et al [ 78 ] studies conducted on the same catchment, they obtained excess discharge because the model wasn't calibrated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6,(a) ). Though the precipitation increment identified in the distant future might result in the flow rate increment, the temperature increment might also result in intensified evapotranspiration, which should lead to a slight peak flow rate decline in the distant future [ 77 ]. Refer to Icyimpaye, [ 79 ] and Icyimpaye et al [ 78 ] studies conducted on the same catchment, they obtained excess discharge because the model wasn't calibrated.…”
Section: Resultsmentioning
confidence: 99%
“…According to Ye et al [ 82 ], the study identified up to 400% and 18% flow rate increments resulting from rainfall variation and land use/cover change, respectively, by the end of the century. The study conducted by Li et al [ 77 ] identified up to 162.47% variation by end-century under ssp245, while the study conducted by Haider et al [ 83 ] identified up to 345.3% change factor under RCP8.5.…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that most hydrological elements would increase under future climate patterns, such as precipitation, temperature, and streamflow. Li et al successfully simulated monthly streamflow in the HRYRB by using the SWAT model and conducted a sensitivity analysis on the model parameters (Li et al, 2022). They found that the monthly streamflow is notably sensitive to changes in precipitation, evaporation, and land cover.…”
Section: Introductionmentioning
confidence: 99%